CD8+ T Cells in SARS-CoV-2 Induced Disease and Cancer—Clinical Perspectives - Mortezaee, Keywan; Majidpoor, Jamal (Frontiers in Immunology, 2022)
Dysregulated innate and adaptive immunity is a sign of SARS-CoV-2 induced disease and cancer. CD8+ T cells are the important cells of immune system. The cells are belonged to the adaptive immunity and take a front-line defense against viral infections and cancer. Extreme CD8+ T cell activity in lung of patients with SARS-CoV-2 induced disease and within tumor microenvironment (TME) will change their functionality into exhausted state and are undergoing apoptosis. Such diminished immunity will put cancer cases at a high-risk group for SARS-CoV-2 induced disease, rendering viral sepsis and a more severe condition which will finally cause higher rate of mortality. Recovering responses from CD8+ T cells is a purpose of vaccination against SARS-CoV-2. The aim of this review is to discuss about CD8+ T cellular state in SARS-CoV-2 induced disease and in cancer and to present some strategies for recovering the functionality of these critical cells.